Methods and Mechanism of Powder Mixing for Selective Laser Melting - Yang, Guang; Xie, Yilian; Zhao, Shuo; Ren, Yuhang; Wang, Chao (Manufacturing Technology Journal, 2022)
Selective laser melting (SLM) technology has strict demand to its powder materials which is needed to be spread evenly and conducted laser sintering layer by layer. Therefore, the uniformity and flatness of powder bed are the basic conditions for processing. Ball milling is an important composite powder preparation process of SLM. Three kinds of ball milling processes, dry ball milling, wet ball milling and hollow milling with various parameters are adopted to prepare TC4 / TiB2 composite powder. It is concluded that a balling time 8 h at a speed of 230 rpm without milling ball is proved the optimal working condition to make the composite powder maintain good spherical shape and ensure the mixing uniformity. The mechanism of three kinds of powder mixing effects is revealed by analyzing the dynamic relationship and hardness of the milling ball, TC4 and TiB2 particle. This work provides an important reference for the preparation of high quality TC4 / TiB2 composite powder for SLM.
Keywords: Ball Milling; Powder Mixing; TC4 / TiB2 composite powder; Selective Laser Melting